Enhancing Financial Literacy among College Athletes - Rubin, Lisa M.; Joseph, Mindy; Lutter, Sonya; Roberts, Daron K.; Jones, Julian J. (My University, 2021)
College students, including athletes, have limited exposure to financial education prior to enrolling in college (Britt et al., 2015). Athletes juggling two full-time roles as athlete and college student have limited time for financial education and the opportunity to work. Some athletes receive athletic scholarships and some do not, but either way, many athletes must seek additional funding and student loans to pay for college. Huston’s (2010) model demonstrated connections between financial literacy, behaviors, and education to serve as a framework for our study. The purpose of this study was to determine college athletes’ subjective and objective financial literacy, how they applied this knowledge, and their preferred mode(s) of financial education to pilot financial literacy education geared specifically for athletes based on their preferences. Data was collected from two institutions in the same Power 5 conference: monthly spending logs, focus groups, interviews, a financial knowledge survey, and pre- and post-tests flanking a financial literacy module in first-year experience courses and summer bridge. A Money 101 course was piloted over eight weeks, and peer financial counseling was offered. As athletes might gain access to their name, image, and likeness (NIL) for potential income in the near future, financial education is paramount.
Keywords: College athletes; Financial education; Financial literacy